2023
DOI: 10.3390/su151310080
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Indicators of Implementation of Sea Transportation Safety Management System for Traditional Shipping Based on Delphi Approach

Abstract: The implementation of the safety management system (SMS) in traditional shipping in Indonesia, known as “Pelra”, has not been implemented. The nature of the operation pattern and characteristics of Pelra, which are still traditional (non-convention), means that international maritime rules such as SOLAS, MARPOL, LLC, Collreg, and STCW, as well as Indonesian government regulations related to shipping safety, are not suitable for Pelra. As a result, Pelra ship accidents continue to occur every year in Indonesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This paper builds on Wahid's research [14], which identified factors and indicators affecting SMS implementation, by quantifying the influence of each factor. Previous studies, such as that of Malisan et al [15], have focused on stability, strength, and human resources.…”
Section: Introductionmentioning
confidence: 99%
“…This paper builds on Wahid's research [14], which identified factors and indicators affecting SMS implementation, by quantifying the influence of each factor. Previous studies, such as that of Malisan et al [15], have focused on stability, strength, and human resources.…”
Section: Introductionmentioning
confidence: 99%